Abrasive water jet machining of coir fiber reinforced epoxy composites: a review. (1st March 2022) - Virk, Gurpreet Singh; Singh, Balkar; Singh, Yadvinder; Sharma, Shubham; Ilyas, R A; Patyal, Vikas
Abstract: Natural-fiber-reinforced composites are progressively attracting interest in the aerospace, automotive, aeronautics, and marine sectors due to their good strength-to-weight ratios, long lifetimes and cost-effectiveness. Traditional machining methods have trouble machining such composite materials. However, abrasive water jet machining (AWJM) provides an alternative quality machining method that can be accomplished by regulating various process variables. The efficiency of the AWJM method has been the subject of extensive study, due to its negligible heat-affected zone. This review attempts to focus on an exploration of the thermal and mechanical properties and the AWJM efficiency of various coir-fiber-based composites in relation to various parameters and to determine the best AWJM operating conditions. There are numerous process variables that influence AWJM machined surface quality. However, the standoff distance, hydraulic pressure, abrasive mass flow rate, nozzle diameter, and transverse speed are all important factors to consider. Kerf taper, kerf width, and surface roughness are considered key response factors.